Research on FE Modeling Methods of Riveting Structure of Steel-aluminum Hybrid Body - WEN Pengzhe; MI Caiying; LI Xiangtao (机车电传动)
In order to establish a simplified finite element model for the riveting structure of steel-aluminum hybrid body, the finite element model of double-row single-plate riveting structure and the finite element model of double-row double-plate riveting structure were established based on ANSYS platform with shell element and MPC184 rigid beam element at three different complexity levels, and these simplified finite element models were analyzed compared with the solid finite element model. The method of discretizing the riveted structure using the shell element and the MPC184 rigid beam element was proposed on this basis, and then it was applied to the strength analysis process of a steel-aluminum hybrid car body successfully. This research showed that, the relative error of the von-Mises stress was less than 5 percent in the region of the riveted structure where the distance from the rivet was greater than ten times the nominal diameter of the rivet when using this method, and it would gradually decrease as the distance increases. In the analysis of the strength of the large riveting structure, the calculation efficiency was greatly improved by using the method and the sub modeling technique ensuring the accuracy of the calculation.